PEEK-Polymer for Dental Implants: A Concise Review - Mitalova, Zuzana; Duplak, Jan; Duplakova, Dariana; Mital, Dusan; Litecka, Juliana (Materiale Plastice, 2024)
The biomaterials applicable in dental implantology, or implantology generally, are subject to specific requirements, namely biocompatibility, osseointegration, resistance to fracture/ oxidative degradation/ long-term compressive stress/ hydrolisis in boiling water, suitable morphology, suitable physical properties (including mechanical properties), aesthetics, etc. When selecting a suitable material for dental implants, it is also necessary to consider the patient s current health condition and possible complications when placing titanium implants and alloys. If there is a risk of an allergic reaction or hypersensitivity to any of the components of the metal prosthesis, the placement of a semi-crystalline thermoplastic implant - called polyetheretherketone, abbreviated PEEK - is a possible option. Such a wide range of stiffness means that PEEK formulations can be produced with modulus values similar to cortical bone. PEEK is classified as a High Performance Polymer of polymer pyramide (such as Polysulfones polybutylene terephthalate). PEEK can be applied for dental abutment and dental body. This article summarises basic information on the structure and properties of PEEK polymer, advantages/ disadvantages (compared to metal - titanium restorations), application and general information from the examined field.